99m-Tc-MDP-scintimammography in the evaluation of breast masses or tumor angiogenesis - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2004)
Background: Vascular endothelial growth factor (VEGF) is a prognostic factor in breast cancer. One of the mechanisms of extra-skeletal uptake of Tc-99m-methylenediphosphonate (MDP) is suggested to be tumor vascularity. We studied the correlation between MDP uptake and VEGF and compared the diagnostic accuracy of mammography versus MDP-scintimammography(MDP-S). Materials and Methods: Fifty-four patients with suspicion of breast cancer were evaluated. Breast images were collected 5-10 minutes after injection of Tc-99m-MDP prior to biopsy. Tissue slides were stained using a rabbit-polyclonal anti-VEGE Results: MDP-S showed a diagnostic accuracy of 83.3% in BIRADS category 4 lesions. Four out of 23 benign lesions were false-positive. The tumor to background (TM/BG) ratio of early images of MDP-S was correlated with VEGF staining (p: 0.014) and with tumor size (p: 0.006). Conclusion: Early images of Tc-99m-MDP-S may satisfactorily identify cancers with increased neovascularization. MDP-S seems to be an accurate imaging modality, especially in BIRADS category 4 lesions.
Keywords: breast cancer; mammography; technetium Tc-99m-medronate; VEGF; ENDOTHELIAL GROWTH-FACTOR; POSITIVE PREDICTIVE-VALUE; TC-99M METHOXYISOBUTYLISONITRILE; MAMMOGRAPHIC FEATURES; CANCER; SCINTIMAMMOGRAPHY; TC-99M-SESTAMIBI; SCINTIGRAPHY; MECHANISMS; CARCINOMA